COVID-19–We urgently need to start developing an exit strategy. (July 2020) - Petersen, Eskild; Wasserman, Sean; Lee, Shui-Shan; Go, Unyeong; Holmes, Allison H.; Al-Abri, Seif; McLellan, Susan; Blumberg, Lucille; Tambyah, Paul
Highlights: Countries need to develop well-planned exit strategies when the COVID-19 pandemic subsides. Abstract: Aim: The purpose of this perspective is to review the options countries have to exit the draconian "lockdowns" in a carefully staged manner. Methods: Experts from different countries experiencing Corona Virus Infectious Disease 2019 (COVID-19) reviewed evidence and country-specific approaches and the results of their interventions. Results: Three factors are essential: 1. Reintroduction from countries with ongoing community transmission; 2. The need for extensive testing capacity and widespread community testing, and 3. An adequate supply of personal protective equipment, PPE, to protect health care workers. Discussed at length are lifting physical distancing, how to open manufacturing and construction, logistics, and the opening of higher educational institutions and schools. The use of electronic surveillance is considered. Conclusion: Each country should decide on the best path forward. However, we can learn from each other, and the approaches are, in reality, very similar.